1985
DOI: 10.1007/bf02187199
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical silica mass balances in Lake Michigan and Lake Superior

Abstract: Silica budgets for Lake Michigan and Lake Superior differ in several respects. Mass balance calculations for both lakes agree with previous studies in that permanent burial of biogenic silica in sediments may be only about 5% of the biogenic silica produced by diatoms. Because dissolution rates are large, good estimates of permanent burial of diatoms can not be obtained indirectly from the internal cycle of silica (silica uptake by diatoms and subsequent dissolution) but must be obtained from the sediment stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…The diatom assemblages of some shallow, highly saline lakes within the NGP dataset may thus not represent the local living community, but the reworking of older, dried sediments from littoral areas during seasonal or interannual lake-level fluctuations. Conversely, increasing water depth might be expected to have a positive effect on preservation where physical mixing is reduced, as in many freshwaters, relatively little dissolution occurs during sedimentation, even over deep, oxic water columns (Schelske et al 1984;Ryves et al 2003). Dissolution in upper sediments may also be enhanced in some shallow NGP lakes from seasonal thermal instability of interstitial waters, leading to a flux of pore water Si to the overlying water column, as has been observed in late summer in shallow, unstratified Canadian lakes (Hecky et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diatom assemblages of some shallow, highly saline lakes within the NGP dataset may thus not represent the local living community, but the reworking of older, dried sediments from littoral areas during seasonal or interannual lake-level fluctuations. Conversely, increasing water depth might be expected to have a positive effect on preservation where physical mixing is reduced, as in many freshwaters, relatively little dissolution occurs during sedimentation, even over deep, oxic water columns (Schelske et al 1984;Ryves et al 2003). Dissolution in upper sediments may also be enhanced in some shallow NGP lakes from seasonal thermal instability of interstitial waters, leading to a flux of pore water Si to the overlying water column, as has been observed in late summer in shallow, unstratified Canadian lakes (Hecky et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In shallow, coastal lakes (salinity 0.2-18 g L 21 ) in Denmark, where salinity is related to marine connectivity rather than evaporative concentration, surface sediment preservation (as assessed using the F index) is positively correlated with (log) salinity (r 5 0.64, n 5 25, p , 0.001; data from Ryves et al 2004). In many freshwater lakes with deep water columns, although most biogenic silica reaches the sediment surface (Schelske et al 1984;Ryves et al 2003), selective dissolution of susceptible taxa can be severe and appears unrelated to salinity. Among the great lakes of East Africa, for example, fine Nitzschia spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the annual cycle of DSi, a normal sequence of events in many lakes and marine systems, should not be confused with long-term historical depletion of the water colunln DSi reservoir. Schelske (1985a) demonstrated that, even though most of diatom production is recycled on an annual basis, only a small percentage of diatom production need be lost in long-residence-time systems in order to effect a major biogeochemical change in the water column.…”
Section: Criticism Of the Silica Depletion Hypothesismentioning
confidence: 99%
“…The regular monitoring of the DSi or N:P:Si ratio is thus important, especially in lakes and estuaries subjected to intense human activities. Several limnological studies suggested that the long-term changes in DSi and diatom blooms can be explained by a shift in a limiting nutrient for diatoms due to P emissions or its constraint (Schelske, 1985;Barbiero et al, 2002;Ko¨hler et al, 2005), but here are few detailed assessments of the effects of Si dynamics on freshwater ecosystems, mainly due to the paucity of Si monitoring relative to N and P (Foundation of River and Watershed Environment Management, 2007).…”
Section: Introductionmentioning
confidence: 99%